Cardiorespiratory Fitness as a Correlate of Cardiovascular, Anthropometric, and Physical Risk Factors: Using the Ruffier Test as a Template - Khalid A. Alahmari; Kanagaraj Rengaramanujam; Ravi Shankar Reddy; Paul Silvian Samuel; Venkata Nagaraj Kakaraparthi; Irshad Ahmad; Jaya Shanker Tedla (Canadian Respiratory Journal)
Background. Assessment of cardiorespiratory fitness (CRF) is a standard procedure in routine clinical practices. Early identification of risk factors through screening is vital in the fight against chronic diseases. Evaluation of CRF can impose cost implications in the clinical setting; thus, a simple and easy-to-use test is to be advocated. The Ruffier test is a simple test that can assess CRF, and it is necessary to find whether the test reflects the effects of compounding factors in CRF. Objective. This study aims to determine the association between CRF (estimated VO2max) with cardiovascular, anthropometric, and physical risk factors using the Ruffier test. Methods. A cross-sectional study with a sample of 52 male participants was conducted. Before the Ruffier test, each participant’s body weight, height, waist circumference, skinfold thickness, thigh length, lower-limb length, thigh circumference, physical activity, blood pressure, smoking, diabetes, and pulmonary functions were recorded, and these factors correlated with CRF. Results. There was a significant inverse relationship found between the estimated VO2max and age, height, body weight, body mass index, waist circumference, a sum of skinfold, fat percentage, thigh length, lower-limb length, thigh circumference, smoking, blood pressure, heart rates, and diabetes p<0.05. A significant positive correlation was found between the estimated VO2max with physical activity and respiratory functions p<0.05. In the multivariable model, body weight and resting heart rate were significantly inversely associated with the estimated VO2maxp<0.05. Conclusion. Using the Ruffier test, various risk factors of CRF are correlated with the estimated VO2max. This test reflects the effects of different compounding factors on CRF; therefore, it can be used in routine clinical practices to identify the risk factors early.